2012
DOI: 10.1088/0953-2048/25/4/045008
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of critical current density of liquid-infiltration-processed Y–Ba–Cu–O bulk superconductors using milled Y2BaCuO5powder

Abstract: The size effects of a precursor Y 2 BaCuO 5 (Y211) powder on the microstructure and critical current density (J c ) of liquid infiltration growth (LIG)-processed YBa 2 Cu 3 O 7−y (Y123) bulk superconductors were investigated in terms of milling time (t). Y211 powders were attrition-milled for 0-10 h in 2 h increments at a fixed rotation speed of 400 rpm. Y211 pre-forms were made by pelletizing the milled Y211 powders followed by subsequent sintering, after which an LIG process with top seeding was applied to t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(8 citation statements)
references
References 22 publications
1
6
0
1
Order By: Relevance
“…The Y0 sample shows the highest T c,on set at 92.8 K compare with samples Y40 and Y80. The T c,on set values are close to standard critical temperature value of YBCO bulk superconductor [22]. The transition temperature width of Y40 and Y80 samples is wider than Y0 sample as the ultra-sonicated time increase and less than 1.5 K as presented in Fig.…”
Section: Resultssupporting
confidence: 70%
“…The Y0 sample shows the highest T c,on set at 92.8 K compare with samples Y40 and Y80. The T c,on set values are close to standard critical temperature value of YBCO bulk superconductor [22]. The transition temperature width of Y40 and Y80 samples is wider than Y0 sample as the ultra-sonicated time increase and less than 1.5 K as presented in Fig.…”
Section: Resultssupporting
confidence: 70%
“…The overall output characteristics observed that the J c value at the LIG‐processed samples increases with an increase of the pre‐form sintering, which was governed by the finer Y‐211 secondary phase size and lower porosity in the Y‐123 products . Further, the size effects of a precursor Y 2 BaCuO 5 (Y211) powder on the microstructure and critical current density ( J c ) of liquid infiltration growth (LIG)‐processed YBa 2 Cu 3 O 7− y (Y123) bulk superconductors were also investigated by Mahmood et al , and found that the onset superconducting transition temperature ( T c,onset ) of all samples, i.e., 0–10 h ball‐milled samples were the same (91.5 K), but the transition width became wider as the ball milling time increased. The maximum J c of 1.0 × 10 5 A cm −2 (at 77 K, 0 T) was achieved when the ball milling time is 8 h, which is attributed to the reduction in pore density and Y211 particle size .…”
Section: Resultsmentioning
confidence: 99%
“…(i) The infiltration growth (IG) process should be employed to fabricate this new Mg-doped NdBCO seed crystal. The IG technique has been proved to be an effective way to prepare large REBCO bulks, and has attracted more and more attention recently because of its advantages compared with the MG method, such as fewer pores and cracks, negligible shrinkage and distortion in the final product, and especially the ability to provide fine-sized spherical RE 2 BaCuO 5 (RE-211) inclusions in the REBa 2 Cu 3 O 7−x (RE-123) matrix, which bring significant improvement in current density [21][22][23][24][25][26][27]. Moreover, in our recent studies, we improved this technique via modification of the liquid source composition and the pellet configuration pattern, in order to simplify the process flow and enhance the experimental stability [28][29][30].…”
Section: Introductionmentioning
confidence: 99%